2016
DOI: 10.1038/ncomms12319
|View full text |Cite
|
Sign up to set email alerts
|

Cellular tagging as a neural network mechanism for behavioural tagging

Abstract: Behavioural tagging is the transformation of a short-term memory, induced by a weak experience, into a long-term memory (LTM) due to the temporal association with a novel experience. The mechanism by which neuronal ensembles, each carrying a memory engram of one of the experiences, interact to achieve behavioural tagging is unknown. Here we show that retrieval of a LTM formed by behavioural tagging of a weak experience depends on the degree of overlap with the neuronal ensemble corresponding to a novel experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 48 publications
1
88
2
Order By: Relevance
“…In humans, behavioral tagging might be more pronounced in tasks that involve explicit memory processes, or spatial navigation, rather than implicit fear conditioning. Future work should consider whether behavioral tagging can rescue weak spatial object learning in humans, which would still be in keeping with several rodent investigations of behavioral tagging (Ballarini et al 2009; Wang et al 2010; Nomoto et al 2016; Moncada 2017).…”
Section: Figurementioning
confidence: 82%
See 2 more Smart Citations
“…In humans, behavioral tagging might be more pronounced in tasks that involve explicit memory processes, or spatial navigation, rather than implicit fear conditioning. Future work should consider whether behavioral tagging can rescue weak spatial object learning in humans, which would still be in keeping with several rodent investigations of behavioral tagging (Ballarini et al 2009; Wang et al 2010; Nomoto et al 2016; Moncada 2017).…”
Section: Figurementioning
confidence: 82%
“…In rodents, this includes tasks for spatial learning (Wang et al 2010), object recognition (Ballarini et al 2009), inhibitory avoidance (Moncada et al 2011), and contextual fear conditioning and extinction (Ballarini et al 2009; de Carvalho Myskiw et al 2013; de Carvalho Myskiw et al 2014; Menezes et al 2015). In the behavioral tagging model, weak learning sets the conditions for a long-term memory; but in line with the synaptic tag-and-capture model (Frey and Morris 1997), long-term memory formation is dependent upon stronger synaptic potentiation within overlapping neural ensemble during a critical time window around the time of training (Nomoto et al 2016). Novelty exploration provides the conditions for strong synaptic potentiation by triggering upregulation of plasticity related proteins in the hippocampus (Straube et al 2003) necessary to stabilize local learning tags set by the weak learning experience.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…If these neurons are directly reactivated (i.e., with light), the memory, or more specifically the behavioral readout of the target memory, can be elicited . If the cells are inhibited, the natural cue‐induced recall of the target memory is impaired . Control experiments have shown that activation and inhibition of these cell ensembles affects the targeted memory specifically, not other similar but nonlabelled memories .…”
Section: “She Would Give Them Order She Would Create Constellations:mentioning
confidence: 99%
“…56,59 If the cells are inhibited, the natural cue-induced recall of the target memory is impaired. 60,61,[66][67][68] Control experiments have shown that activation and inhibition of these cell ensembles affects the targeted memory specifically, not other similar but nonlabelled memories. 56,[58][59][60] If the labelled neural ensembles are destroyed, so too is the memory.…”
Section: Technical Strategies Transgeneexpressionmentioning
confidence: 99%